A Viewpoint: Validation of Self-Reported Anxiety Screening Scales in Perinatal Populations– Outstanding Issues in the Validation Research Agenda. Issue 3 (September 2021) - Adhikari, Kamala; Bright, Katherine; Metcalfe, Amy; Patten, Scott
In the absence of perinatal anxiety screening, clinically significant symptoms of anxiety remain under-detected and undertreated during perinatal period. Perinatal anxiety has a significant and far reaching impact on mothers and their children. There are well established recommendations for routine mental health screening during the perinatal period, yet less than one in five of providers routinely screen and one in seven women receive the mental health intervention they need. The validity of anxiety screening scales needs to be ascertained by criterion validity parameters such as sensitivity, specificity, and predictive values. Criterion validity, which is assessed against a reference standard, allows clear interpretation of screening results, supporting their integration with clinical care pathways. However, few existing validation studies of anxiety scales in perinatal populations examined criterion validity. Construct validity of anxiety scales, the focus of existing validation studies, does not use reference standard; thus, it lacks clear clinical interpretability for screening application. Future validation studies should focus on assessing the criterion validity of anxiety scales in perinatal populations. This will help nurses, midwives, and other members of interdisciplinary teams to clarify scale validity, interpretation, and utility for screening women for anxiety in the perinatal period.